1991
DOI: 10.21273/hortsci.26.9.1149
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Microsprinklers Improve Protection of Citrus Trees in an Advective Freeze

Abstract: The severe advective freeze of 23-26 Dec. 1989 killed most nonprotected trees in Florida's northern citrus region. Minimum temperatures reached - 8.3C with >43 hours below freezing. Microsprinklers elevated to a height of 0.6 or 0.9 m and placed inside the canopy of young `Hamlin' and navel orange trees [Citrus sinensis (L.) Osb.] provided excellent protection to heights well above 1 m. Initial survival height of trees with emitters elevated to 0.9 m was higher than has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Microsprinkler irrigation uses sensible heat and the latent heat of fusion of water to maintain tree temperatures at or above 0°C. After early failures in development of this approach, it has gained wide popularity in commercial groves in the southeastern United States (Bourgeois and Adams, 1987;Bourgeois et al, 1990;Braud et al, 1981;Nesbitt et al, 2000;Parsons et al, 1991;Rieger et al, 1985). Use of microsprinkler irrigation for young trees to protect the lower trunk is similar in effect to soil banking but easier to implement once the system is established.…”
Section: Freeze Protection Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Microsprinkler irrigation uses sensible heat and the latent heat of fusion of water to maintain tree temperatures at or above 0°C. After early failures in development of this approach, it has gained wide popularity in commercial groves in the southeastern United States (Bourgeois and Adams, 1987;Bourgeois et al, 1990;Braud et al, 1981;Nesbitt et al, 2000;Parsons et al, 1991;Rieger et al, 1985). Use of microsprinkler irrigation for young trees to protect the lower trunk is similar in effect to soil banking but easier to implement once the system is established.…”
Section: Freeze Protection Measuresmentioning
confidence: 99%
“…One major limitation of this approach is the need for large quantities of water. In some areas, water is limited, which has stimulated research to identify the minimum amount required to maintain tree survival (Bourgeois and Adams, 1987;Bourgeois et al, 1990;Braud et al, 1981;Nesbitt et al, 2000;Parsons et al, 1991;Rieger et al, 1985). In Alabama, groundwater is currently not limiting in many parts of the southern counties where satsumas are grown.…”
Section: Freeze Protection Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Water-based cold protection of crops has been extensively used in Florida since the1960s (Harrison et al, 1974). Studies in Florida citrus groves have reported the benefits of using water for cold protection (Parsons et al, 1982(Parsons et al, , 1985(Parsons et al, , 1991a(Parsons et al, , 1991b. Research on the beneficial effects of using water for cold protection of other crops grown outdoors such as apples and strawberries has also been conducted (Heinemann et al, 1992;Koc et al, 2000;Stombaugh et al, 1992).…”
mentioning
confidence: 99%
“…Work in Florida has shown that microsprinklers can, indeed, be effective in major freezes (Oswalt and Parsons, 1981;Parsons et al, , 1982 and are less expensive to install in new groves than solid-set sprinklers. Even when the risk of evaporative cooling was high in low-humidity, windy freezes, microsprinklers provided some protection (Parsons et al, 1985(Parsons et al, , 1991Parsons and Wheaton, 1987). Drip irrigation provided virtually no freeze protection.…”
mentioning
confidence: 99%